2016
DOI: 10.3791/54012-v
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Culture and Transduction of Adult Mouse Cardiomyocytes

Abstract: Cultured cardiomyocytes can be used to study cardiomyocyte biology using techniques that are complementary to in vivo systems. For example, the purity and accessibility of in vitro culture enables fine control over biochemical analyses, live imaging, and electrophysiology. Long-term culture of cardiomyocytes offers access to additional experimental approaches that cannot be completed in short term cultures. For example, the in vitro investigation of dedifferentiation, cell cycle re-entry, and cell division has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…The isolation and culture of adult mouse cardiomyocytes follow the established procedures. 23,24 The pcDNA3.1-E4bp4 plasmid (Addgene 34572) 25 was cotransfected with a green fluorescent protein plasmid. Radioactive isotope tracer studies were as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…The isolation and culture of adult mouse cardiomyocytes follow the established procedures. 23,24 The pcDNA3.1-E4bp4 plasmid (Addgene 34572) 25 was cotransfected with a green fluorescent protein plasmid. Radioactive isotope tracer studies were as described previously.…”
Section: Methodsmentioning
confidence: 99%
“…Atrial cardiomyocytes isolated from lethally irradiated Ldlr −/− mice with hematopoietic-specific inactivation of Tet2 or WT controls were incubated with a fluorescent calcium sensitive indicator, Fluo-3 AM, to visualize and quantitatively characterize calcium transients (Figure 5 D), as previously described. 48 , 49 Atrial cardiomyocytes from mice with hematopoietic-specific inactivation of Tet2 had dysfunctional intracellular calcium handling resulting in a trend ( P =0.055) toward a prolonged transient time to peak, and an increased frequency of spontaneous calcium release events after removal of depolarizing stimuli (Figure 5 E through 5 G). Release of calcium from the SR is predominantly mediated by RyR2; thus, SR calcium stores can provide an approximation of RyR2 activity.…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the cannulation of the heart through the proximal aorta can be quite difficult, but it is an essential step to wash and fix the organ properly. Judd et al 17 , showed how to perform this step effectively. Moreover, the degassing procedure needed by the CLARITY protocol is quite complex too, but it is essential for tissue preservation; if this step is not performed properly, the tissue could encounter damages and decay during the incubation in clearing solution.…”
Section: Discussionmentioning
confidence: 99%